Evaluation of poisoning attended to the Regional Deaching Hospital of Cajamarca, from january 2012 to december 2018 - Díaz-Barco, José (2021)
To evaluate the cases of poisoning by drugs and other toxic agents, treated at the Cajamarca Regional Teaching Hospital, from January 2012 to December 2018, patients of all ages, of both sexes, who were admitted for some reason, were considered. form of poisoning to the Emergency Service and the information on clinical cases of poisoning was taken from the files kept in the Statistics Service of the hospital, the data collected was processed in an updated SPSS statistics version 25 package, where they were Data in simple tables, in addition to graphics for each table, the Microsoft Excel 2016 program was also used, obtaining the graphics and their interpretation according to the data provided for processing.The information collected from January 2012 to December 2018, it was found that the age group with the highest prevalence was 18-29 years, and the one with the lowest prevalence was 0-11 years; regarding sex: male (373 cases) versus female (175 cases); by the type of chemical substance or agent causing the intoxication, ethyl alcohol occupies the first place (412 clinical cases), followed by pesticides and drugs (55 and 53 cases) respectively and considering the severity of the poisonings these were: 294 mild 219 moderate, 24 severe and 11 fatal. The present study allows us to infer that poisoning in the population continue to be a serious Public Health problem, so it is appropriate to communicate the results to the authorities of the Health Directorate so that they take the pertinent actions and strengthen prevention, diagnosis, and timely treatment to mitigate the morbidity and mortality rate.